Sharpe vs Treynor: Strategies for evaluating stock portfolio performance on the Indonesian Stock Exchange - Thersia M M Da Silva; Petrus E de Rozari; Darwin Zebua; Efandri Agustian (Universitas Nusa Cendana, 2026)
This study investigates whether the Sharpe Ratio and Treynor Ratio produce significantly different portfolio performance rankings in the Indonesian stock market. A quantitative research design was employed using a sample of 11 large-capitalization companies representing each IDX-IC sector listed on the Indonesia Stock Exchange during the 2020–2024 period. An optimal portfolio was constructed under a 0%–30% asset allocation constraint, and portfolio performance was assessed using the Sharpe Ratio and Treynor Ratio. Differences in portfolio rankings were examined through descriptive, comparative, and paired t-test analyses. The optimized portfolio generated an expected return of 74.60%, with a Sharpe Ratio of 5.60 and a Treynor Ratio of 0.0697. The paired t-test yielded a p-value of 0.331, indicating no statistically significant difference between the rankings produced by the two performance measures. These findings suggest that, for well-diversified portfolios in which unsystematic risk has been effectively diversified away, the Sharpe Ratio and Treynor Ratio provide comparable assessments of investment performance. This study extends the evidence on risk-adjusted portfolio evaluation in an emerging market context and provides practical implications for investors and portfolio managers in selecting appropriate performance measurement approaches. Keywords: Sharpe Ratio; Treynor Ratio; Portofolio Performance; Indonesian Stock Exchange